2020
DOI: 10.1002/jgm.3205
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of motor and behavioral activity in Sandhoff mice transplanted with human CD34+ cells transduced with a HexA/HexB expressing lentiviral vector

Abstract: Background Tay–Sachs and Sandhoff disease are debilitating genetic diseases that affect the central nervous system leading to neurodegeneration through the accumulation of GM2 gangliosides. There are no cures for these diseases and treatments do not alleviate all symptoms. Hematopoietic stem cell gene therapy offers a promising treatment strategy for delivering wild‐type enzymes to affected cells. By genetically modifying hematopoietic stem cells to express wild‐type HexA and HexB, systemic delivery of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The work presented here highlights our effort to develop the use of HSPC transduced with a lentiviral vector expressing Ube3a , in an innovative preclinical model of AS, which offers a promising strategy for life-long delivery of functional UBE3A through the hematopoietic system to the brain. This cross-correction approach has been successfully demonstrated for other monogenic diseases including adrenoleukodystrophy, metachromatic leukodystrophy and Sandhoff disease ( 22 , 31 , 32 , 49 ). In previous studies, successful engraftment of gene-modified microglia in the brains of treated mice demonstrated that HSPC gene therapy can deliver therapeutic proteins to disease-affected cells ( 22 , 30 , 32–34 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented here highlights our effort to develop the use of HSPC transduced with a lentiviral vector expressing Ube3a , in an innovative preclinical model of AS, which offers a promising strategy for life-long delivery of functional UBE3A through the hematopoietic system to the brain. This cross-correction approach has been successfully demonstrated for other monogenic diseases including adrenoleukodystrophy, metachromatic leukodystrophy and Sandhoff disease ( 22 , 31 , 32 , 49 ). In previous studies, successful engraftment of gene-modified microglia in the brains of treated mice demonstrated that HSPC gene therapy can deliver therapeutic proteins to disease-affected cells ( 22 , 30 , 32–34 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This cross-correction approach has been successfully demonstrated for other monogenic diseases including adrenoleukodystrophy, metachromatic leukodystrophy and Sandhoff disease ( 22 , 31 , 32 , 49 ). In previous studies, successful engraftment of gene-modified microglia in the brains of treated mice demonstrated that HSPC gene therapy can deliver therapeutic proteins to disease-affected cells ( 22 , 30 , 32–34 , 49 ). In our current study, we observed elevated levels of UBE3A in the brains of the Ube3a-HET treatment group, and rescue of motor, cognitive and EEG phenotypes following transplantation and engraftment of the genetically modified human CD34+ HSPC as neonates or adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the role of the immune system, a cohort of age-and sex-matched YACNSG mice were given a human immune system at postnatal day 2-5 following previously established protocols. [23][24][25] The humanized YACNSG were then longitudinally assessed alongside the parental YAC128 strain and nonhumanized YACNSG. Following assessment of the level of "humanization", functional assessment began at 4 months and was continued until the mice were 12 months old.…”
Section: Discussionmentioning
confidence: 99%
“…Humanization of YACNSG mice followed established protocols. [23][24][25] Briefly, human CD34+ hematopoietic stem and progenitor cells (HSPC) were isolated from umbilical cord blood obtained from the UC Davis Umbilical Cord Collection Program by Ficoll-Paque (GE Healthcare, Logan, Utah) density gradient. They were further purified by CD34 magnetic bead column separation (Miltenyi Biotec, Auburn, California).…”
Section: Humanization Of Yacnsg Micementioning
confidence: 99%